26th ACM Symposium on Virtual Reality Software and Technology 2020
DOI: 10.1145/3385956.3418944
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Social Touch in Multi-User Virtual Reality

Abstract: Figure 1: Participants performed the interactions depicted above with a physically remote research assistant in VR. We compared the emotional experience of the two intimacy groups (high vs. low intimacy) regarding the influence of intimacy, direction of touch and sex of participant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…For example, according to [28] using a vest equipped with multiple vibrotactile actuators, body location led to reactions similar to those observed in the case of physical touch, although this was not gender related. Yet studies reported in [21,34,71] seem to suggest the opposite, i.e. similarity in responses between physical and digital touch were related to dyad's gender.…”
Section: How Is Affective Touch Created and Interpreted?mentioning
confidence: 83%
See 1 more Smart Citation
“…For example, according to [28] using a vest equipped with multiple vibrotactile actuators, body location led to reactions similar to those observed in the case of physical touch, although this was not gender related. Yet studies reported in [21,34,71] seem to suggest the opposite, i.e. similarity in responses between physical and digital touch were related to dyad's gender.…”
Section: How Is Affective Touch Created and Interpreted?mentioning
confidence: 83%
“…Issues of control and privacy emerged as critical and somewhat inter-related in remote communication since the typical means to enact them are partially lost [65,80]. The study in VR [71] showed that the direction of initiation of touch (i.e., who in the dyad initiated touch) has a strong effect on a variety of emotions (e.g., anxiety, disgust, happiness). Our participants sought the possibility to explicitly control not just touch but also which haptic channels were left open for reception.…”
Section: Sense Of Control and Privacymentioning
confidence: 99%
“…This non-parametrical rank-based test was elaborated to analyse longitudinal data in factorial designs with the aim to investigate treatment effects, time effect and their interaction effects. Indeed, this analysis estimates the relative treatment effects (RTEs), comparable to the concept of relative marginal effects (for more information about the analysis and the nparLD R package, see Noguchi et al, 2012; for a similar application of WTS on repeated measures data see Soto et al, 2020;Sykownik & Masuch, 2020). However, repeated measures designs are conceptually included in longitudinal designs, since one of their characteristics is the inclusion of several measurements of the same variable collected on the same participant.…”
Section: Discussionmentioning
confidence: 99%
“…HMD-based virtual reality has the potential to become a technology-mediated mode of communication that can psychologically feel near identical to face-to-face interaction (Rosedale, 2016). There is potential to achieve this via advancements in motion capture technology and haptic devices (Pan & Hamilton, 2018;Pan & Steed, 2019;Parger et al, 2020;Seymour et al, 2019;Sykownik & Masuch, 2020). Future research is needed to fast-track the development of this new mode of social interaction.…”
Section: Discussionmentioning
confidence: 99%